IDENTIFICATION OF RELAXATION TECHNIQUES: STRESS AND HABITS OF MUSCLE EXPANSION (Fiep Bulletin - online, 2015)
This assignment is part of the research carried through in doctorate level, through which we investigate if the students from graduation of Physical Education of three universities on the region of Campinas, has scientific knowledge about prolongation techniques, seen the importance of this subject matter in the intervention of the professional. At the present work we focus the study made concerning the phenomenon: Stress/Relaxation/Stretching, constituting first the concept, process and control of the stress, where we approach diverse relaxation techniques that use muscular stretch, for relief tensions generated for daily stress. Different considerations had been reviewed searching agreement for this study and about the set of final considerations to this respect, we find that the experience of stretch exercises, makes possible a bigger state of tunning with the own body, as well as the balance of tensions, related to the reduction of stress, propitiating a general welfare of the body. As conclusion, about the professional qualification of the student to take care of a great parcel of the society, front to the development of the prolongation exercises, it is necessary to be considering the existence of this subject, in a specific and scientific way, in the professional preparation in Physical Education.
Keywords: muscular prolongation; stress; professional formation